Human Factors in Intelligent Vehicles. - Olaverri-Monreal, Cristina, 1970-; García-Fernández, Fernando; Rossetti, Rosaldo J. F. (River Publishers series in transport technology., 2020)
Human Factors in Intelligent Vehiclesaddresses issues related to theanalysis of human factors in the design and evaluation of intelligent vehiclesfor a wide spectrum of applications and over different dimensions. Thecontributors cover autonomous vehicles as well as the frameworks for analyzingautomation, modelling and methods for road users' interaction such asintelligent user interfaces, including brain-computer interfaces and simulationand analysis tools related to human factors.